Gender Stereotyping and Self-Stereotyping Attitudes: A Large Field Study of Managers - Tor Eriksson; Nina Smith; Valdemar Smith (Institute of Labor Economics (IZA), 2017)
The dearth of women in top managerial positions is characterized by a high persistence and insensitivity to changes and differences in institutions and policies. This suggests it could be caused by slowly changing social norms and attitudes in the labor market, such as gender stereotypes and gender identity. This paper examines gender stereotypes and self-stereotyping in a large cross section of (about 2,970) managers at different job levels in (1,875) Danish private-sector firms. The survey data used contain detailed information about the managers as well as their employers. We find significant gender differences between managers with regard to gender stereotyping attitudes. Male managers on average tend to have stronger gender stereotype views with respect to the role as a successful manager than their female peers. However, female CEOs' gender stereotypes do not differ from their male peers' and have significantly more pronounced masculine stereotypes than female managers at lower levels. Female managers have stronger beliefs in their own managerial abilities regarding feminine skills and weaker beliefs in their masculine skills, whereas the opposite is observed for male managers. Gender stereotypes and self-stereotypes vary across types of managerial employees and firms. Beliefs in own ability could explain at most ten percent of the observed gender differential in C-level executive positions.
Keywords: J16; D83; D84; M51; 330; glass ceiling effects; gender; self-stereotypes; stereotypes; managerial labor markets